Time between Diagnosis and Treatment of Hypopharynx and Larynx Cancer: Are Longer Delays Associated with Higher Discrepancy between Clinical and Pathological Staging? - Santos, Mariline; Monteiro, Eurico (International Archives of Otorhinolaryngology, 2020)
Introduction At the time of diagnosis, treatment strategies for cancer are largely based upon clinical staging. However, discrepancy between clinical and pathological staging has been reported.Objective To assess the rate of staging discrepancy in Laryngeal and Hypopharyngeal Squamous Cell Carcinoma (LHSCC), the potential influence of higher interval of time from diagnosis to primary surgical treatment, and whether this has any impact on survival outcomes.Methods Retrospective study of patients with LHSCC proposed for primary surgical treatment.Results The study population included 125 Caucasian patients with LHSCC. The level of agreement between clinical and pathological tumor staging was moderate (Cohen’s Kappa: 0.400; p < 0.001) and similar result was found for node staging (Cohen’ Kappa: 0.520; p < 0.001). The mean time between diagnosis and surgical treatment was 26.66 days and no statistically significant influence was found with staging discrepancy. The sample presented a 5-year Overall Survival (OS) of 58.2% and a Disease-specific survival (DSS) of 72.6%. No statistically significant impact of staging discrepancy on survival was found.Conclusion For advanced LHSCC, based on the findings of physical examination, endoscopy and imaging, is possible to achieve a moderate accuracy between clinical and pathological staging which allows a reliable counselling and treatment planning. Interval of time under 3–4 weeks between diagnosis and surgical treatment does not influence the rate of discrepancy. However, almost 30% of staging discrepancy is expected due to false negatives of imaging and limitations of physical exams.
Keywords: survival; laryngeal cancer; hypopharyngeal cancer; cancer staging